VO#057 Quotation for the special-shaped planter bench work rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the quotation for the special-shaped planter bench work of BRACU new campus project.